TRAINING OF FUTURE ENERGY SPECIALISTS TO SOLVE PRACTICAL PROBLEMS ON THE BASIS OF PHYSICAL PROJECTS - Наталя Сосницька; Олена Кривильова (Фізико-математична освіта)
Formulation of the problem. In the field of higher education, general and special competencies are acquired, which have in common the ability to apply knowledge in practical situations. Therefore, the formation of mental and practical skills and abilities of future energy specialists to solve practical problems is becoming more and more important.